Manipulação discursiva e crise de Estado como obstáculos à institucionalização dos direitos fundamentais no Brasil - Silva, Luciano Tertuliano da (2015)
The academic work seeks to demonstrate how the interconnection between power, law and State reflects, in Brazil, vicious and enduring consequence of non-compliance with fundamental rights since the oxides from the colonial period up to the present moment, finding the causes in the political system and legal, pointing them and addressing them specifically. Thorough historical analysis will reveal the manipulation of fundamental rights by governments as a way of curbing of movements of social uprising, misrepresenting the true essence and aim to dignify the human person in its fullness, this practice rooted in the political system and reiterated throughout the time, especially in the current social context. The cessation of this vicious circle is presented the institutionalization of fundamental rights as a mechanism to achieve effective and lasting of these rights, which consists in transforming these rights in first State reason, in their actual material existence